If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3(2x + -1) + -4(x + 2) = 5(2x + 3) + -7(x + -2) Reorder the terms: 3(-1 + 2x) + -4(x + 2) = 5(2x + 3) + -7(x + -2) (-1 * 3 + 2x * 3) + -4(x + 2) = 5(2x + 3) + -7(x + -2) (-3 + 6x) + -4(x + 2) = 5(2x + 3) + -7(x + -2) Reorder the terms: -3 + 6x + -4(2 + x) = 5(2x + 3) + -7(x + -2) -3 + 6x + (2 * -4 + x * -4) = 5(2x + 3) + -7(x + -2) -3 + 6x + (-8 + -4x) = 5(2x + 3) + -7(x + -2) Reorder the terms: -3 + -8 + 6x + -4x = 5(2x + 3) + -7(x + -2) Combine like terms: -3 + -8 = -11 -11 + 6x + -4x = 5(2x + 3) + -7(x + -2) Combine like terms: 6x + -4x = 2x -11 + 2x = 5(2x + 3) + -7(x + -2) Reorder the terms: -11 + 2x = 5(3 + 2x) + -7(x + -2) -11 + 2x = (3 * 5 + 2x * 5) + -7(x + -2) -11 + 2x = (15 + 10x) + -7(x + -2) Reorder the terms: -11 + 2x = 15 + 10x + -7(-2 + x) -11 + 2x = 15 + 10x + (-2 * -7 + x * -7) -11 + 2x = 15 + 10x + (14 + -7x) Reorder the terms: -11 + 2x = 15 + 14 + 10x + -7x Combine like terms: 15 + 14 = 29 -11 + 2x = 29 + 10x + -7x Combine like terms: 10x + -7x = 3x -11 + 2x = 29 + 3x Solving -11 + 2x = 29 + 3x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-3x' to each side of the equation. -11 + 2x + -3x = 29 + 3x + -3x Combine like terms: 2x + -3x = -1x -11 + -1x = 29 + 3x + -3x Combine like terms: 3x + -3x = 0 -11 + -1x = 29 + 0 -11 + -1x = 29 Add '11' to each side of the equation. -11 + 11 + -1x = 29 + 11 Combine like terms: -11 + 11 = 0 0 + -1x = 29 + 11 -1x = 29 + 11 Combine like terms: 29 + 11 = 40 -1x = 40 Divide each side by '-1'. x = -40 Simplifying x = -40
| 37.9=7c-9 | | 17x+5y=-7 | | 4/5(y-1/9)=2/5(y+5) | | 6+9i=0 | | 8=3a-1 | | 4+8n=7n+3 | | -1.5w+4.2=-3.2w-2.6 | | 5(5x+9)=25x+45 | | 4n-7=5(2n+7) | | -4(6y-8)-y=-2(y-2) | | 2x-3=3(1-x) | | 950+700+5x=800+400+10x | | 7/8=y-1/6 | | x=60x+259240 | | 12+4(z-3)=-5z+5 | | 1.4(z+0.5)=0.7(z-13) | | 3/2c+4=15 | | 5x^2+28+15=0 | | (-20/30)27/30 | | -5x-19=-13 | | 5*3/4*1/3 | | 2x(-3)=6 | | 7b/4+5=54 | | 12-2(7+2t)=2(t-1) | | 5x^2=42x+27 | | 3y+x=-16 | | 3y+x=-16 | | (4x-5)/(3x+7) | | 4(4-8y)-y=3y+7 | | 2/3c+4=15 | | f(x)=-3 | | 8=3c-7 |